Pokes, Sunburn, and Hot Sauce: Drosophila as an Emerging Model for the Biology of Nociception - Im, Seol Hee (2011)
The word “nociception” is derived from the Latin “nocere,” which means “to harm.” Nociception refers to the sensory perception of noxious stimuli that have the potential to cause tissue damage. Since the perception of such potentially harmful stimuli often results in behavioral escape responses, nociception provides a protective mechanism that allows an organism to avoid incipient (or further) damage to the tissue. It appears to be universal in metazoans as a variety of escape responses can be observed in both mammalian and non-mammalian vertebrates, as well as diverse invertebrates such as leeches, nematodes, and fruit flies (Sneddon [2004] Brain Research Review 46:123–130; Tobin and Bargmann [2004] Journal of Neurobiology 61:161–174; Smith and Lewin [2009] Journal of Comparative Physiology 195:1089–1106). Several types of stimuli can trigger nociceptive sensory transduction, including noxious heat, noxious chemicals, and harsh mechanical stimulation. Such high-threshold stimuli induce the firing of action potentials in peripheral nociceptors, the sensory neurons specialized for their detection (Basbaum et al. [2009] Cell 139:267–284). In vertebrates, these action potentials can either be relayed directly to a spinal motor neuron to provoke escape behavior (the so-called monosynaptic reflex) or can travel via spinal cord interneurons to higher-order processing centers in the brain. This review will cover the establishment of Drosophila as a system to study various aspects of nociceptive sensory perception. We will cover development of the neurons responsible for detecting noxious stimuli in larvae, the assays used to assess the function(s) of these neurons, and the genes that have been found to be required for both thermal and mechanical nociception. Along the way, we will highlight some of the genetic tools that make the fly such a powerful system for studies of nociception. Finally, we will cover recent studies that introduce new assays employing adult Drosophila to study both chemical and thermal nociception and provide an overview of important unanswered questions in the field.